2024
DOI: 10.1029/2023gl107652
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Water and Ocean Topography Mission: A Breakthrough in Radar Remote Sensing of the Ocean and Land Surface Water

Lee‐Lueng Fu,
Tamlin Pavelsky,
Jean‐Francois Cretaux
et al.

Abstract: The elevations of water surfaces hold important information on the earth's oceans and land surface waters. Ocean sea surface height is related to the internal change of the ocean's density and mass associated with ocean circulation and its response to climate change. The flow rates of rivers and volume changes of lakes are crucial to freshwater supplies and the hazards of floods and drought resulting from extreme weather and climate events. The Surface Water and Ocean Topography (SWOT) Mission is a new satelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Arrival of early data from the SWOT mission has shown that the SSH variability observed by the satellite exceeds mission requirements in the submesoscale band at wavelengths below 25 km (Figure 1 in [3]). Special attention in SWOT calibration has focused on removing systematic errors caused by the uncertainties in the geometry and orientation of the on-board interferometer, which provides the largest contribution to the SWOT error budget [7].…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arrival of early data from the SWOT mission has shown that the SSH variability observed by the satellite exceeds mission requirements in the submesoscale band at wavelengths below 25 km (Figure 1 in [3]). Special attention in SWOT calibration has focused on removing systematic errors caused by the uncertainties in the geometry and orientation of the on-board interferometer, which provides the largest contribution to the SWOT error budget [7].…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, it still keeps its superior skill in retrieving the true state at a significantly better (2 times) level (Figure 6). It is noteworthy that such situations (large background errors at small scales) are unlikely in the open ocean, because both modeling [39] and the latest SWOT observations [3] indicate that the SSH spectrum falls steeply with the wavenumber so that respective background errors should barely exceed 5 cm at scales below 5 km.…”
Section: Computational Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The Surface Water and Ocean Topography (SWOT) satellite mission was designed to resolve SSHA at wavelengths down to ~15 km [4,5]. A recent study shows that SWOT's 2 km 2 data product appears to achieve about three times better resolution [6]. The 2 km data product is derived from 250 m native grid data.…”
Section: Introductionmentioning
confidence: 99%
“…The SWOT mission was launched in December 2022 to measure the high-resolution, 2-dimensional sea surface height (SSH) field based on the Ka-band radar interferometer (KaRIn) instrument (Fu et al, 2024;Morrow et al, 2019). Compared to the ∼50-km noise floor achieved by the conventional nadir altimeters, KaRIn has an order-of-magnitude lower noise floor at 5-km wavelength and, averaged globally, its rms noise level is estimated to be around 0.25 cm on a 1 km-by-1 km grid posting (Fu et al, 2024).…”
Section: Introductionmentioning
confidence: 99%